2023
DOI: 10.1108/md-05-2022-0694
|View full text |Cite
|
Sign up to set email alerts
|

Ethical leadership and employee unethical behavior: a dual-processing model

Abstract: PurposeThis study seeks to apply a dual-processing model to understand how ethical leadership prohibits employee unethical behavior through both employee deontic justice and distributive justice.Design/methodology/approachA survey research was conducted with 62 supervisors and 244 subordinates of 17 firms collected at 2 time points separated by approximately 3 weeks in People's Republic of China.FindingsA multilevel modeling analysis was used to test the dual-processing model. The results showed that both empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The results revealed that all 35 items formed five distinct factors (job performance, seven items; perceived internal CSR, five items; perceived external CSR, ten items; perceived organizational support, eight items; collectivism, five items). The confirmatory factor analysis model also demonstrated acceptable model fit ( χ 2 /df = 1.21, RMSEA = 0.03, CFI = 0.97, IFI = 0.97, TLI = 0.97, SRMR = 0.05, p < 0.01) (Gan et al. , 2023; Bagozzi and Yi, 2012; Hu and Bentler, 1999).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The results revealed that all 35 items formed five distinct factors (job performance, seven items; perceived internal CSR, five items; perceived external CSR, ten items; perceived organizational support, eight items; collectivism, five items). The confirmatory factor analysis model also demonstrated acceptable model fit ( χ 2 /df = 1.21, RMSEA = 0.03, CFI = 0.97, IFI = 0.97, TLI = 0.97, SRMR = 0.05, p < 0.01) (Gan et al. , 2023; Bagozzi and Yi, 2012; Hu and Bentler, 1999).…”
Section: Resultsmentioning
confidence: 82%
“…The confirmatory factor analysis model also demonstrated acceptable model fit (χ 2 /df 5 1.21, RMSEA 5 0.03, CFI 5 0.97, IFI 5 0.97, TLI 5 0.97, SRMR 5 0.05, p < 0.01) (Gan et al, 2023;Bagozzi and Yi, 2012;Hu and Bentler, 1999).…”
Section: Regression Analysismentioning
confidence: 81%